2017
DOI: 10.1111/liv.13397
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and severity of fibrosis in nonalcoholic fatty liver disease: An age‐dependent risk profiling study

Abstract: Among patients with NAFLD, the metabolic profiles associated with risk for severe fibrosis varied among age groups. Low HDL, obesity and IFG/diabetes were prevalent among patients in the lower and middle age tertiles. HDL and IFG/diabetes but not visceral obesity were prevalent among those in the highest age tertile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
40
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 39 publications
(105 reference statements)
9
40
4
1
Order By: Relevance
“…Previous studies have reported that an increase in liver stiffness is independently associated with metabolic syndrome in the general population 29 and that visceral obesity and diabetes are associated with severe hepatic fibrosis. 30 Thus, the present findings are consistent with previous findings. Petta et al reported that low HDL cholesterol is associated with severe hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Previous studies have reported that an increase in liver stiffness is independently associated with metabolic syndrome in the general population 29 and that visceral obesity and diabetes are associated with severe hepatic fibrosis. 30 Thus, the present findings are consistent with previous findings. Petta et al reported that low HDL cholesterol is associated with severe hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, of the four components of metabolic syndrome, the presence of central obesity, and an elevation of blood pressure and fasting plasma glucose levels were associated with an increase in advanced hepatic fibrosis. Previous studies have reported that an increase in liver stiffness is independently associated with metabolic syndrome in the general population and that visceral obesity and diabetes are associated with severe hepatic fibrosis . Thus, the present findings are consistent with previous findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations